Analysis on Factors Influencing Geography Teachers’ Ability in Constructing High-Order Thinking Skills (HOTS) Assessment Instrument - Suhendro Suhendro; Dede Sugandi; Mamat Ruhimat (Geosfera Indonesia, 2021)
The teacher's ability to construct assessment instruments is a focus that needs to be considered. Furthermore, the demand of the 21st century directs teachers to set questions that are oriented to train students' abilities in higher-order thinking. However, several factors affect the ability to construct HOTS-oriented assessment instruments. This study aims to investigate what factors influence geography teachers’ ability to develop higher-order thinking skills (HOTS) instruments to measure learning outcomes. This study used a survey method with a quantitative approach. The data collection technique was field observation, and multiple linear regression was used for analysis. The results showed the linearity of teacher education regarding the length of teaching geography was 0.904, the tertiary institution was 0.009, and the background of education was 0.019. Also, teachers' certification was 0.007, their training was 0.032, and their experience in making HOTS questions was 0.047. The coefficient value of determination R, namely 0.635 means the relationship between teaching length, the linearity of their education in tertiary institutions, background, certification, training, and experience regarding the ability to develop HOTS-oriented assessment instruments is 63.5%. This means the relationship is strong, and 36.5% is another factor. This study concludes that the factors that significantly affect the ability of geography teachers in developing HOTS-oriented assessment instruments are the linearity factor of teacher education in universities, education background, certification, teacher training and experience in making HOTS questions. Keywords: Teacher ability factors; Assessment, Higher-order thinking skills Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License